Anthropogenic warming impacts on California snowpack during drought. Issue 5 (15th March 2017) - Berg, Neil; Hall, Alex
Abstract: Sierra Nevada climate and snowpack is simulated during the period of extreme drought from 2011 to 2015 and compared to an identical simulation except for the removal of the twentieth century anthropogenic warming. Anthropogenic warming reduced average snowpack levels by 25%, with middle‐to‐low elevations experiencing reductions between 26 and 43%. In terms of event frequency, return periods associated with anomalies in 4 year 1 April snow water equivalent are estimated to have doubled, and possibly quadrupled, due to past warming. We also estimate effects of future anthropogenic warmth on snowpack during a drought similar to that of 2011–2015. Further snowpack declines of 60–85% are expected, depending on emissions scenario. The return periods associated with future snowpack levels are estimated to range from millennia to much longer. Therefore, past human emissions of greenhouse gases are already negatively impacting statewide water resources during drought, and much more severe impacts are likely to be inevitable. Key Points: Anthropogenic warming reduced average snowpack levels by 25%, with middle‐to‐low elevations experiencing reductions between 26 and 43% Return periods associated with anomalies in 4 year 1 April SWE are estimated to have doubled, and possibly quadrupled, due to past warming Further snowpack declines of 60–85% are expected, depending on emissions scenario